2020
DOI: 10.1186/s12891-020-03728-x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroma of tendon sheath of the hand in a 3-year-old boy: a case report

Abstract: Background Fibroma of tendon sheath (FTS) is a rare benign soft tissue tumor that often occurs in the upper extremities. It manifests as a slow-growing mass, often without tenderness or spontaneous pain. FTS occurs most commonly in people aged 20–40 years and is extremely rare in young children. Because FTS presents with atypical physical and imaging findings, it might be misdiagnosed as another soft tissue tumor such as a ganglion cyst or tenosynovial giant cell tumor (TSGCT). Although marginal resection is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…Fibroma of the tendon sheath, also called synovial tendon sheath fibroma [ 8 ], consists of a benign proliferation of fibroblasts that are firmly attached to the tendon or tendon sheath and are sometimes attached to the articular capsule [ 9 ]. In the study that Chung and Enzinger published about 138 cases of FTS, and the peak age was in the third to fifth decades of life with a male preponderance.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroma of the tendon sheath, also called synovial tendon sheath fibroma [ 8 ], consists of a benign proliferation of fibroblasts that are firmly attached to the tendon or tendon sheath and are sometimes attached to the articular capsule [ 9 ]. In the study that Chung and Enzinger published about 138 cases of FTS, and the peak age was in the third to fifth decades of life with a male preponderance.…”
Section: Discussionmentioning
confidence: 99%
“…It manifests clinically as a slow-growing tumor, potentially painful. 1 The treatment of choice is marginal resection of the lesion, which has a high recurrence rate. 2 We present the case of a TSF in the finger of a 6-year-old girl.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroma of tendon sheath is a benign uncommon soft tissue tumor that presents as a solitary, firm, slow-growing painless nodule [1] . This tumor arises from the synovium of the tendon sheath that occurs mostly around small joints such as the fingers, hands, and wrist [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The case reports which we reviewed examined the pediatric patients they ranged in age from 8-17. In a case series of 138 patients, it was shown that only 20% of fibroma of tendon sheath cases were diagnosed in children and upper extremity involvement occurred in 86% of cases [1,2] . When juvenile cases of FTS are identified, older children and adolescents are more commonly affected [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation